2021
DOI: 10.33050/atm.v5i2.1532
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religiosity as a Mediating Variable in the Relationship between Online Transactions and Customer Satisfaction and Loyalty in Islamic Banking

Abstract: This study aims to determine the role of religiosity as mediation in the relationship between online transactions and customer satisfaction and loyalty in Sharia banking in the Jakarta area. The population of this research is all sharia banking customers in Jakarta. The number of samples in this study was 175 Sharia banking customers in Jakarta by sampling purposive sampling method. The data processing method used is Structural Equation Modelling. The results showed: 1) there is no effect of failure on the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The results of the previous research described above and summarized in the table below show that both conceptually and actually, waqf is needed as an instrument in the economy to improve people's welfare [31]. The research conducted in this study is different from previous research in terms of research objects and research methods but has similarities to research conducted by using the Theory of Planned Behavior (TBP) [32].…”
Section: Tabarru' Contractmentioning
confidence: 81%
“…The results of the previous research described above and summarized in the table below show that both conceptually and actually, waqf is needed as an instrument in the economy to improve people's welfare [31]. The research conducted in this study is different from previous research in terms of research objects and research methods but has similarities to research conducted by using the Theory of Planned Behavior (TBP) [32].…”
Section: Tabarru' Contractmentioning
confidence: 81%
“…A few studies that have examined the moderation effect of religiosity on loyalty have reported mixed results. Sunaryo et al (2020) and Purnama et al (2021) found a positive and significant moderation effect of religiosity in the relationships between SQ and loyalty and between CS and loyalty, respectively. Aslam et al (2022) indicate a significant moderation effect of religion between corporate image and loyalty.…”
Section: Introductionmentioning
confidence: 92%
“…Prior studies that discussed customer satisfaction in Islamic business discussed customer satisfaction of Islamic bank customers. These studies have been carried out by Ahmed et al (2022), De Bruin et al (2021), Fida et al (2020, Zouari & Abdelhedi (2021), Aini (2018), Jawaid et al (2021), Rama (2020), Mariyanti et al (2021), Haron et al (2020, Jan & Shafiq (2021), Purnama et al (2021), Safi et al (2020), Syaifuddin et al (2022), Anouze et al (2019), andRiduwan et al (2022). Research on consumer satisfaction in Islamic banks is analyzed using the SERVQUAL framework (Ali & Raza, 2017;De Bruin et al, 2021;Janahi & Al Mubarak, 2017;Zouari & Abdelhedi, 2021).…”
Section: Exploration Determinants Of Customer Satisfactionmentioning
confidence: 99%